Extracellular vesicles from cancer cell lines of different origins drive the phenotype of normal oral fibroblasts in a CAF-like direction - Søland, Tine M.; Lipka, Aleksandra; Ruus, Ann-Kristin; Molværsmyr, Ann-Kristin; Galtung, Hilde K.; Haug, Trude M. (Frontiers in Oncology, 2024)
IntroductionNormal oral fibroblasts (NOFs) are located in the connective tissue of the oral mucosa. The NOFs play an important role in wound healing, tumor progression, and metastasis. They are subjected to influence by external and internal stimuli, among them extracellular vesicles (EVs), that are considered as important players in cell to cell communication, especially in carcinogenesis and metastatic processes. During tumorigenesis, stromal NOFs may undergo activation into cancer-associated fibroblasts (CAFs) that modify their phenotype to provide pro-oncogenic signals that in turn facilitate tumor initiation, progression, and metastasis. The aim of the study was to reveal the effect of EVs derived from local (oral squamous cell carcinoma – OSCC) and distant (pancreatic adenocarcinoma – PDAC; malignant melanoma brain metastasis – MBM) cancer origin on NOFs and their possible change into a CAF-like direction.MethodsThe effect of each of the cancer EV types on NOFs proliferation, viability, and migration was tested. Also, changes in gene expression of the well-established CAF biomarkers ACTA2, FAP, PDGFR, and two putative CAF biomarkers, the Ca2+- activated ion channels ANO1 and KCNMA, were studied.ResultsObtained results indicate that NOFs receive and process signals transmitted by EVs originating from both OSCC, PDAC, and MBM. The fibroblast response was dependent on EV origin and concentration, and duration of EV exposure.ConclusionThe present results indicate that the molecular cargo of the EVs direct NOFs towards a pro-tumorigenic phenotype.